Connection Between Aspects of Algebraic Creative Thinking of Undergraduate Students of Mathematics Education Study Program - ., Rochmad; Kharis, Muhammad; Agoestanto, Arief; Zahid, Muhammad Zuhair (KnE Social Sciences, 2019)
This article was prepared based on qualitative research, case studied with research subjects 36 undergraduate students of mathematics education study program FMIPA UNNES in elementary linear algebra. Intended to ﬁnd out students’ problem solving abilities aspects of algebraic creative thinking and to describe connections between aspects of students creative thinking in solving problems. Aspects of creative thinking include: ﬂuency, ﬂexibility, novelty, and elaboration. Data obtained through tests, observations, and interviews. Based on the analysis of the test results, as many as 17 students reached the minimal criteria which is at least 61, and 15 students worth under 61. This indicates that many students had difﬁculty in solving problems of elementary linear algebra that contain aspects of creative thinking. The creative thinking character ofstudentsinsolvingproblemsofelementaryalgebrawithaspectsofcreativethinking; based on data analysis, obtained information that students in solving problems generally tend to thought on aspects of ﬂuency. Some students had difﬁculty thought intermsofﬂexibility.Onlyafewstudentsthoughtofthenoveltyaspect.Manystudents had difﬁculty thought about aspects of elaboration. In connection between aspects of creative thinking there were several sequence patterns in thought when solving problems. Only a few of the four aspects of creative thinking were patterned on the minds of students. Keywords: acute toxicity, tomato extract, liver histopathology